1959
DOI: 10.1099/00221287-21-2-344
|View full text |Cite
|
Sign up to set email alerts
|

The Propagation and Preservation of Eperythrozoon coccoides

Abstract: SUMMARY : The propagation of Epe ythroxoon coccoides in embryonated hen eggs inoculated by the yolk sac and intravenous routes is recorded. Fourteen continuous serial passages were made in the yolk sac and sixteen passages were made after intravenous inoculation into the chick embryo. The mortality among infected embryos was low; splenic enlargement was the only lesion detected. Once the strain had become established. E . coccoides was seen in blood smears taken from some eggs after each passage. Yolk sac or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1965
1965
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…“Sheep kidney culture” and “mixed hamster kidney-bovine lymphatic tissue culture” media were both unsuccessful in cultivating M. ovis . However, Seamer ( 1959 ), successfully passaged Eperythrozoon coccoides 14 times by yolk sac inoculation and 16 times by intravenous injection of the chick embryo. Ershaduazzaman and Iskandar ( 2001 ), using embryonated chicken eggs, successfully passaged M. ovis through the yolk sac and maintained its attachment to the red blood cell in heparinised samples by incubation in Eagle’s medium supplemented with inosine and bovine foetal serum under 5% CO 2 .…”
Section: Diagnosis Of Mycoplasma Ovismentioning
confidence: 99%
“…“Sheep kidney culture” and “mixed hamster kidney-bovine lymphatic tissue culture” media were both unsuccessful in cultivating M. ovis . However, Seamer ( 1959 ), successfully passaged Eperythrozoon coccoides 14 times by yolk sac inoculation and 16 times by intravenous injection of the chick embryo. Ershaduazzaman and Iskandar ( 2001 ), using embryonated chicken eggs, successfully passaged M. ovis through the yolk sac and maintained its attachment to the red blood cell in heparinised samples by incubation in Eagle’s medium supplemented with inosine and bovine foetal serum under 5% CO 2 .…”
Section: Diagnosis Of Mycoplasma Ovismentioning
confidence: 99%
“…For these tests mice about 3 or 4 months old are most suitable since an infection rate representative of the colony will not have developed in very young mice and will be more difficult to demonstrate with increasing age. In this connexion the fact should be stressed that E. coccoides is readily transmissible to intact mice and that parasitaemia is easily demonstrable; indeed, we have utilized this characteristic of E. coccoides as the basis of much experimental work over many years (Niven et al 1952;Seamer, 1959). SUMMARY 1.…”
Section: Discussionmentioning
confidence: 99%
“…coccoides has not been cultivated on artificial media. Derrick et al (1954) found E. coccoides survived up to 9 days in embryonated chicken eggs but attempts at passage were unsuccessful; serial passages in embryonated chicken eggs have been reported (Seamer, 1959) but not confirmed. The standard procedure for determining whether a mouse colony was infected was to splenectomize a dozen 3-to 4-month-old mice and examine their blood daily (Gledhill et al, 1965b).…”
mentioning
confidence: 99%